GENDER DIFFERENCES IN EMERGENT WRITING USING SALT TRAY: WHO IS SUPERIOR? - Fidrayani Fidrayani (Jurnal Harkat : Media Komunikasi Gender, 2022)
Abstract. This study aims to determine gender differences in writing ability initially using salt tray learning media in group A. Type of research used is pre-experimental research with the design design of one pre-test post-test group, which is an experiment carried out in one group without a comparison group. The results of the study there were significant differences, obtained a value of 0.000 < 0.05. So it can be concluded that there is a gender difference between women who are more dominant than men in the ability to write initially using salt tray learning media in early childhood.Keywords: salt tray; writing competence; gender perspective; early childhood Abstrak. Penelitian ini bertujuan untuk mengetahui perbedaan gender pada kemampuan menulis awalnya menggunakan media pembelajaran baki garam pada anak usia dini.  Jenis penelitian yang digunakan adalah penelitian pra-eksperimen dengan desain satu kelompok post-test pre-test, yaitu eksperimen yang dilakukan dalam satu kelompok saja tanpa adanya kelompok pembanding.  Hasil penelitian terdapat perbedaan yang signifikan, diperoleh nilai 0,000 < 0,05. Sehingga dapat disimpulkan bahwa terdapat perbedaan gender antara perempuan yang lebih dominan dibandingkan laki-laki dalam kemampuan menulis pada awalnya menggunakan media pembelajaran baki garam pada anak usia dini.Kata Kunci: kompetensi menulis; jenis kelamin; salt-tray